Transcending Hegemonic Phallic-Culture and Imaginaries: Afropolitan Feminism and Relocation as an Emancipatory Metaphor - Okwudiri Anasiudu (Journal of Language and Literature, 2022)
The representation of the struggles of contemporary African women from low-income/middle-class families, and their attempt at breaking free from the hold of such struggles have not gained much attention in the criticism of recent African novels. To bridge this research gap, this study interrogates Helon Habila‘s Travellers; NoViolet Bulawayo‘s We Need New Names; and Chimamanda Adichie‘s Americanah. It underscores the experiences of Darling, Ifemelu, and Mary, as existential struggles which allegorize real-life challenges of low-income/middle-class contemporary African women, and their attempt to break free from the bounds of such challenges aggravated by a hegemonic phallic culture and imaginaries. Adopting a qualitative content-based analytic method and a conceptual framework anchored on the conflated term Afropolitan-feminism; the study demonstrates how the characters’ dissatisfaction with patriarchal exertions and their local geography animated by limited existential opportunities spurred their desire to relocate outside Africa. Importantly, their relocation constitutes a signature of action which could be read as an emancipatory metaphor for transcending those hegemonic structures, norms, worldviews, and imaginaries which militate against twenty-first-century African women's quest for agency.